Assessing Inflammation in Acute Intracerebral Hemorrhage with PK11195 PET and Dynamic Contrast‐Enhanced MRI. Issue 2 (24th October 2017) - Abid, Kamran A.; Sobowale, Oluwaseun A.; Parkes, Laura M.; Naish, Josephine; Parker, Geoff J.M.; du Plessis, Daniel; Brough, David; Barrington, Jack; Allan, Stuart M.; Hinz, Rainer; Parry‐Jones, Adrian R.
ABSTRACT: BACKGROUND AND PURPOSE: Studies in animal models suggest that inflammation is a major contributor to secondary injury after intracerebral hemorrhage (ICH). Direct, noninvasive monitoring of inflammation in the human brain after ICH will facilitate early‐phase development of anti‐inflammatory treatments. We sought to investigate the feasibility of multimodality brain imaging in subacute ICH. METHODS: Acute ICH patients were recruited to undergo multiparametric MRI (including dynamic contrast‐enhanced measurement of blood‐brain barrier transfer constant ( K trans ) and PET with [ 11 C]‐( R )‐PK11195). [ 11 C]‐( R )‐PK11195 binds to the translocator protein 18 kDa (TSPO), which is rapidly upregulated in activated microglia. Circulating inflammatory markers were measured at the time of PET. RESULTS: Five patients were recruited to this feasibility study with imaging between 5 and 16 days after onset. Etiologies included hypertension‐related small vessel disease, cerebral amyloid angiopathy (CAA), cavernoma, and arteriovenous malformation (AVM). [ 11 C]‐( R )‐PK11195 binding was low in all hematomas and 2 (patient 2 [probable CAA] and 4 [AVM]) cases showed widespread increase in binding in the perihematomal region versus contralateral. All had increased K trans in the perihematomal region (mean difference = 2.2 × 10 −3 minute −1 ; SD = 1.6 × 10 −3 minute −1 ) versus contralateral. Two cases (patients 1 [cavernoma] and 4 [AVM]) had delayed surgery (3 and 12 months post‐onset, respectively) with biopsies showing intense microglial activation in perilesional tissue. CONCLUSIONS: Our study demonstrates for the first time the feasibility of performing complex multimodality brain imaging for noninvasive monitoring of neuroinflammation for this severe stroke subtype.